Percy Jackson and the olympians: The titan's curse - Riordan, Rick (New York: Disney . Hyperion, 2007)
" A fast and funny tale, full of action, wisecracks, and superhuman powers."
English
Keywords: Fiction; Greek myth - Fiction; Action - Fiction; Laughs -Fiction.